MARXISM, EDUCATION AND HUMAN EMANCIPATION - Elza Margarida de Mendonça Peixoto (Germinal : Marxismo e Educação em Debate, 2013)
The article recovers in Marxism, (a) the method for the apprehension of the objective conditions for the production of the notion of freedom at different historical conjunctures, (b) the conception of emancipation that will be built in the stage of development of the productive forces and these relations of production in capitalism as a mode of production. In this process, is recovered the notion of emancipation as a possible historical project with the end of class society, when men reach the realm of freedom for self-determination according to your needs. Established a horizon, resumes the role of teachers as organic intellectuals who work aligned to the working class as a class for itself, inside the capitalist school, resisting and ensuring to the working class the access to knowledge accumulated by humanity, focused on the historical and critical perspective.